Environmental influences on shoot and root growth in banana and plantain - Blomme, Guy; Swennen, Rony L.; Tenkouano, A. (2005)
Studies on the influence of environmental conditions on Musa plant growth have predominantly focused on dessert bananas (Musa AAA group). The effect of location, field within location and planting date on shoot and root traits of field-grown flowering plants of 6 Musa spp. genotypes belonging to 4 Musa groups was determined in this study. Results show that Musa spp. are highly sensitive to environmental changes and that soil structure, soil fertility and water regime can have significant effects on productivity. In consequence comparison of growth performance of different varieties can only be done for plants grown under exactly the same conditions